Disseminated intravascular coagulation and subdural haemorrhage: complications from conservative management of placenta increta. Issue 2 (11th October 2016) - Wong, Jolin; Kon, Nicolas Kam King; Tan, Wei Ching
Summary: Conservative management of placenta accreta, though largely successful, can potentially result in significant morbidity, including sepsis or post‐partum haemorrhage. It can produce potentially debilitating consequences, including significant non‐obstetric haemorrhage. We report the rare event of disseminated intravascular coagulation with spontaneous concomitant cranial and spinal subdural haemorrhage arising from the conservative management of placenta increta. We discuss subsequent investigation and management to control the consumptive coagulopathy and prevent further neurological deterioration.